Analysis of Public Perceptions About Islamic Banking Case study in Sekamis Village - Sintia Delvianti; Jevi Saputra (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2023)
The development of Islamic banks is now progressing no less than conventional banks. Conventional banking is more known as interest rate system while Islamic banking adopts profit sharing system. The problem facing Islamic banking today is that the public's knowledge of Islamic banking is still low due to the existence of conventional banking products, so Islamic banking is still viewed by eyes. The purpose of this study was to find the local community’s perception about Islamic banking in Sekamis village, Cermin Nan Gedang district, the capital city of Sarolangun. The research method used is a qualitative field study with a descriptive research approach. The results show that the respondents' level of knowledge about Sharia banks in Sekamis village is not good. Most of the public does not know and it is often difficult to distinguish between a Shariah bank and a regular bank, not only in terms of contracts but also in terms of products, systems and benefits. Generally, if the public knows about it, then the public will be interested in becoming a customer of Sharia banks as they are based on Islamic Sharia principles. And the community only knows about the existence of Islamic banks, but people do not understand the details of Islamic banks. However, only some people understand Islamic banking, and there are also people who do not understand Islamic banking at all. Most people do not know what products are available in Islamic banks. The lack of understanding of the community in Sekamis village is due to the lack of information obtained and the lack of access of Islamic banks in conducting socialization in the village.